Predictors of intention to continue using the internet banking services : an empirical study of current users - Huam, Hon Tat; Md. Nor, Khalil (2008)

(untitled)
The Internet presents the banking industry with an electronic and remote distribution channel. Wherease many studies examined the intention to use Internet banking, this study investigates predictors of intention among current users to continue using the services. Questionnaires were distributed to 210 residents in Klang Valley, Malaysia, of whom 204 (97.1%) responded to the survey. The findings demonstrated that, among the predictors tested, trust was found to be the strongest predictor of intention to continue using Internet banking, followed by compatibility and ease of use. Recommendations to Internet banking service providers and discussions for future study are provided